Nightmares are not the only negative dreams: dream content in individuals who suffer from frequent nightmares - Paul, Franc; Alpers, Georg W.; Reinhard, Iris; Schredl, Michael (Dreaming, 2021)
Previous research found that nightmares are accompanied by strong negative emotions. However, nonnightmare dream content of individuals who frequently suffer from nightmares has never been examined. Eighteen individuals with frequent nightmares (≥1 nightmare/week) and 18 control participants without nightmares (<1 nightmare/month) were examined while sleeping at home in their usual environment with an ambulatory polysomnographic sleep recording system attached. They were asked to report dream content after spontaneous awakenings during 3 consecutive nights. This resulted in 157 dream reports that were subjected to dream content analysis by 2 trained research assistants. We compared nightmare and especially nonnightmare dream content and emotions within the nightmare group, as well as between nightmare and control participants. Also, we quantified references to the research setting in the dream reports. Results revealed more negative and fewer positive emotions in nonnightmare dreams of the nightmare group compared with the control group, even when waking anxiety scores were controlled for. Nightmares were rated as containing more negative affect and more anxiety compared with both, matched nonnightmare dreams of the same individuals and normal dreams of control participants. Furthermore, dreams of individuals who suffer from frequent nightmares contained fewer dream characters compared with control participants’ dreams. Considerably fewer references to the research setting were found compared with prior sleep laboratory studies on dream content. In conclusion, it was found that individuals who frequently suffer from nightmares also experience their usual nonnightmare dreams as more negatively toned. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
Gesehen am 14.10.2021